Cross-country differences in productivity: the role of allocation and selection - Eric J. Bartelsman; John Haltiwanger; Stefano Scarpetta (Institute for the Study of Labor (IZA), 2009)
This paper combines different strands of the productivity literature to investigate the effect of idiosyncratic (firm-level) policy distortions on aggregate outcomes. On the one hand, a growing body of empirical research has been relating cross-country differences in key economic outcomes, such as productivity or output per capita, to differences in policies and institutions that shape the business environment. On the other hand, a branch of empirical research has attempted to shed light on the determinants of productivity at the firm-level and the evolution of the distribution of productivity across firms within each industry. In this paper, we exploit a rich source of data with harmonized statistics on firm level variation within industries for a number of countries. Our key empirical finding is that there is substantial variation in the within-industry covariance between size and productivity across countries, and this variation is affected by the presence of idiosyncratic distortions. We develop a model in which heterogeneous firms face adjustment frictions (overhead labor and quasi-fixed capital) and idiosyncratic distortions. We show that the model can be readily calibrated to match the observed cross-country patterns of the within-industry covariance between productivity and size and thus help to explain the observed differences in aggregate performance.
Keywords: E02; L11; L16; L2; L25; O4; O57; 330; Firm heterogeneity; productivity; allocation of resources; distortions; Unternehmensentwicklung; Produktivität; Wirtschaftspolitik; Allokation; Wirkungsanalyse; Welt